Dual antithrombotic therapy using potent antiplatelet inhibitors in atrial fibrillation and acute coronary syndrome: a randomized controlled trial - Konstantinos D. Rizas; Konstantinos Mourouzis; Dominik Rath; Christoph B. Olivier; Laura Elisa Villegas Sierra; Theofanis Korovesis; Amin Polzin; Amani Al Tawil; Reza Wakili; Lukas von Stuelpnagel; Katharina Mayer; Marion Janisch; et al. (Nature Medicine, 2026)
Abstract The selection of the optimal antithrombotic regimen in patients with atrial fibrillation and acute coronary syndrome remains challenging. Previous trials have demonstrated that dual antithrombotic therapy (DAT), consisting of direct oral anticoagulants (DOACs) plus a P2Y12 inhibitor, reduces bleeding compared to a triple-therapy regimen using vitamin K antagonists. However, subsequent meta-analyses have suggested an increased risk of ischemic events with DAT, particularly within the first month of treatment. Clopidogrel has been the predominant P2Y12 inhibitor used across these studies, despite the risk of high on-treatment platelet reactivity when using this drug. In this study, we conducted an open-label, randomized controlled trial (EPIDAURUS) in patients with atrial fibrillation and acute coronary syndrome, designed to assess the efficacy and safety of a 1-month regimen of DOAC plus potent P2Y12 inhibitor (prasugrel or ticagrelor) compared to DOAC plus clopidogrel and in-hospital aspirin. The primary outcomes of the trial were an efficacy endpoint, recurrent ischemic events and safety endpoints, including death and major bleeding, which were evaluated 6 weeks after randomization using separate win−loss ratio analyses. The study was prematurely terminated after enrollment of 602 patients (154 female) of an expected 1,474 patients, owing to safety concerns raised by the Data and Safety Monitoring Board. Exploratory analyses of secondary safety endpoints, including bleeding type ≥2 and ≥3 according to the Bleeding Academic Research Consortium scale, revealed that, compared to clopidogrel and in-hospital aspirin, treatment with a potent P2Y12 inhibitor was associated with higher bleeding rates without a clear reduction in the risk of ischemic complications. These findings do not support the routine use of potent P2Y12 inhibitors in combination with DOACs in this patient population. ClinicalTrials.gov identifier: NCT04981041 .